A role model for China?: exchange rate flexibility and monetary policy in Japan - Gunther Schnabl; Christian Danne (Center for Economic Studies and ifo Institute (CESifo), 2007)
Few papers have tried to project how Chinese monetary policy will behave under flexible exchange rates. As Japan provides an important role model for China, this paper studies the role of the yen/dollar exchange rate for Japanese monetary policy after the shift of Japan from a fixed to a floating exchange rate regime. The econometric estimations allow for regime shifts in the impact of the exchange rate on monetary policy. The results show that the exchange rate had a substantial impact on Japanese monetary policy in periods of appreciation. This implies rising uncertainty and that repeated attempts to soften the appreciation pressure by interest rate cuts have led Japan into the liquidity trap.
Keywords: E43; E52; E58; F31; F41; 330; Geldpolitik; Flexibler Wechselkurs; US-Dollar; Wechselkurs; Japan; China